Microscopic generalization of the standard interacting boson model Hamiltonian in the restricted dynamics approach - Alcaras, JAC; Tambergs, J.; Ruza, J.; Krasta, T.; Katkevicius, O. (Iop Publishing Ltd, 1996)
The evaluation of the microscopic generalized interacting boson model (GIBM) Hamiltonian, deduced from the general microscopic nuclear Hamiltonian via the collective O-A-1 invariant microscopic Hamiltonian of the general restricted dynamics model (RDM) in the case of central multipole and multipole-Gauss type effective NN-potential is briefly discussed. The GIBM version, which includes all sixth-order terms in the expansion of the collective part of the NN-potential, has been obtained. This GIBM Hamiltonian contains additional terms compared with the standard (sd-boson) interacting boson model (IBM). The microscopic expressions for the standard IBM Hamiltonian parameters in terms of the employed effective NN-potential parameters have also been obtained.